A New Genus of the Tribe Mesostenini From Chile (Hymenoptera, Ichneumonidae). (1963) - Porter, Charles C.
Abstract : In my work on the Chilean Mesostenini it early became evident that the Cryptus cyanipennis of Brullé, one of the most striking and easily recognizable of the described mesostenines of temperate South America, is sufficiently distinct from other known forms to deserve separate generic status. I therefore give below a description of this new genus together with a brief discussion of its affinities and a redescription of the type species.